New Generalizations of Soft LC-Spaces - Ali, Haider Juber; Mahmood, Sabiha I. (Iraqi Journal of Science, 2022)
In this article, we introduce a new type of soft spaces namely, soft  spaces as   a generalization of soft paces. Also, we study the weak forms of soft  spaces, namely, soft  spaces, soft  spaces, soft  space, and soft  spaces. The characterizations and fundamental properties related to these types of soft spaces and the relationships among them are also discussed.